Ensuring Human Rights in the Era of Artificial Intelligence: Ukraine and Practice of ECHR - Volodymyr Gorbalinskiy; Ivan Draliuk; Vitalii Bondarchuk; Serhii Myroslavskyi; Volodymir Manhora (Universitas Airlangga, 2023)
Artificial intelligence gets into all spheres of life which are familiar to us. Automation and optimization of various processes make our daily tasks much easier. The topicality of the research is due to the rapid development and improvement of artificial intelligence, and therefore it is important to familiarize yourself with all aspects of its application. In the course of the study, laws of Ukraine, the practice of the ECHR, as well as international legal documents was analysed. This research is aimed at determining all aspects of the use of artificial intelligence in various spheres of society, its impact on the ways to protect human rights within the framework of these legal relations. The study pays particular attention to the risks which exist in connection with handling of personal information from artificial intelligence, the extent of the impact on our privacy rights, our freedoms and our opportunities. The research is based on issues of the application of artificial intelligence, for example, on solving problems with discrimination, inequality and various social issues. Furthermore, the proposals for the development of legal aspects of the protection of human rights in the context of artificial intelligence at the Ukrainian and international levels are formulated. This research is very important for understanding and developing effective measures to protect our rights and freedoms in this new technological world.